'The Darroch affair': Assemblage lines, components, and transformations. (January 2021) - Clark, Julian
Abstract: This article examines the underresearched role of lines and components in recomposing geopolitical assemblages. It does so by focusing on a single body at the middle of an event to show how its lines of assembling conditioned wider transformations. The event in question – the leaking of confidential diplomatic materials in July 2019 as part of the so-called "Darroch Affair" – opened a massive rift between governing and bureaucratic arms of the UK state. Set in the context of ongoing struggles to recode the transatlantic diplomatic assemblage (TADA) by US and UK governments, Sir Kim Darroch, British Ambassador to the US, was at front and centre of the resulting leaks imbroglio. Using assemblage thinking, I offer an alternative conceptualisation of Darroch's body as distributed across the TADA via structurally complex lines of assembling. I argue the historical trajectories of these lines accelerated assemblage recompositions as the excessiveness of events led to Darroch's body occupying more and more possibility spaces across the TADA. The article considers how the linear complexity of Darroch's body arose, and the consequences of the resulting recompositions of the TADA for its nested diplomatic worlds. Highlights: Examines assemblage recomposition and transformation via lines and components. Analyses how assemblage lines condition components in relation to specific events. Shows resulting de- and recompositions impact the stability and coherence of diplomatic milieux.